Improvement of the Public Transport Route for Line 7103 in Lima: Reduction of Travel Time - Fabian Garay Naveros, Marcelo (2024)
The primary objective of this research wasto propose a modification to the current route of bus 7103, in order to decrease the total travel time for the users. The methodology employed was based on the application of the Bureau of Public Roads (BPR) function to calculate travel times for both the original route and the segments proposed by this study. These proposed sections are chosen with criteria based on their proximity to potential commercial areas, minimizing deviation from the original route, avoiding significant impacts on the circulation of other vehicles, among others. The main results revealed that the current total travel time is 245minutes, whereas the proposed route would have an estimated time of 228 minutes, representing a reduction of 17 minutes, equivalent to a 7% decrease.